Способи творення термінів нанотехнологій - Кримець, Оксана Михайлівна (Харківський національний педагогічний університет імені Г. С. Сковороди, 2024)
У статті розглядаються шляхи виникнення спеціальних назв нанотехнологій – запозичення та морфологічне термінотворення. Досліджено способи термінологічних запозичень – транслітерація, калькування, транслітерація + калькування, а також морфологічний спосіб утворення спеціальних назв нанотехнологій – афіксація, що відбувається шляхом приєднання префіксів та суфіксів латинської, давньогрецької та української мови. Встановлені найпоширеніші значення префіксів та суфіксів, які застосовуються для творення термінів досліджуваної галузі.

The article examines the topical problem of developing nanotechnology terminology: borrowing terms from other languages and forming special units by combining morphemes according to specific word-formation models. The research aims to find the ways of terminological borrowings and consider the morphological way of creating the terms of the researched field. The task is to characterize the ways of borrowing terms, to determine the semantic characteristics of prefixes and suffixes involved in thе formation of new special names of nanotechnologies. As a result of the research, it is found that the terms of nanotechnology are borrowed by transliteration, calquing, and in a mixed way – transliteration + calquing. Special units borrowed through transliteration preserve the internal and external form of the term of the producer language and, at the same time, undergo phonetic, graphic, and morphological changes and thus adapt to the norms of the Ukrainian literary language. In calquing, a direct pomorphemic translation of a foreign term occurs. As a result of the mixed method of borrowing (transliteration + calquing), hybrid terms arise, which include both borrowed (transliterated) and Ukrainian bases, which are the result of literal translation of elements of a foreign language term. Nanotechnology terms also arise due to the morphological way of creation, namely by affixation using Latin, ancient Greek and Ukrainian prefixes and suffixes, which most often mean process, location or negation. Thus, the presented methods of term formation demonstrate that at the current stage of the development of the terminology of nanotechnology there is a tendency towards its internationalization, which is connected with the growth of the communicative function of the term. From the point of view of dissemination and exchange of scientific and technical information, this trend is positive, but from the point of view of the development of national terminology, it is negative; therefore, in cases where there is a Ukrainian term, it is worth using it, as well as giving preference to Ukrainian prefixes and suffixes in the process of translation or formation of new special names in the field of nanotechnology.
Methods of creating nanotechnology terms
Keywords: термінологія нанотехнологій; запозичення термінів; калькування; транслітерація; морфологічне термінотворення; суфікси; префікси; terminology of nanotechnology; borrowing of terms; calquing; transliteration; morphological term formation; suffixes; prefixe